2009
DOI: 10.1099/ijs.0.004325-0
|View full text |Cite
|
Sign up to set email alerts
|

Delimitation of the species of the Debaryomyces hansenii complex by intron sequence analysis

Abstract: The delineation of species among strains assigned to Debaryomyces hansenii was examined using a gene genealogies-based approach in order to compare spliceosomal intron sequences found in four housekeeping genes (ACT1, TUB2, RPL31 and RPL33). This revealed four distinct groups of strains containing, respectively, D. hansenii var. hansenii CBS 767 T , D. hansenii var. fabryi CBS 789 T , Candida famata var. flareri CBS 1796 T (the anamorph of D. hansenii var. fabryi CBS 789 T ) and Debaryomyces tyrocola CBS 766 T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
32
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 40 publications
7
32
1
Order By: Relevance
“…In the present study we applied a polyphasic approach to reexamine and taxonomically characterize several yeasts from the ACBR culture collection that demonstrated an affiliation to D. hansenii in our previous studies. Similarly to the already published data (Groenewald et al, 2008;Jacques et al 2009;Nguyen et al 2009), our results showed that the phylogeny based on the sequences of 5.8S-ITSs regions and D1/D2 domain is not sufficient for reliable identification of the Debaryomyces species (Fig. 1A).…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…In the present study we applied a polyphasic approach to reexamine and taxonomically characterize several yeasts from the ACBR culture collection that demonstrated an affiliation to D. hansenii in our previous studies. Similarly to the already published data (Groenewald et al, 2008;Jacques et al 2009;Nguyen et al 2009), our results showed that the phylogeny based on the sequences of 5.8S-ITSs regions and D1/D2 domain is not sufficient for reliable identification of the Debaryomyces species (Fig. 1A).…”
Section: Discussionsupporting
confidence: 67%
“…On the basis of the considerable differences of RAPD patterns, Prillinger et al (1999) proposed that the two species D. hansenii and D. fabryi should be reinstated. These results have recently been confirmed by different fingerprinting techniques (PCR and IGS AluI fingerprinting) and phylogenetic analysis of ACT1, TUB2, RPL31 and RPL33 sequences (Groenewald et al, 2008;Jacques et al, 2009;Nguyen et al, 2009 (Groenewald et al, 2008;Jacques et al, 2009;Nguyen et al, 2009). These studies have also indicated that genetic exchanges are not rare among the closely related Debaryomyces species, explaining the high genetic diversity and hybrid nature of several isolates (Jacques et al, 2009;Nguyen et al, 2009).…”
Section: Introductionsupporting
confidence: 49%
See 2 more Smart Citations
“…An increasing number of examples have been recently reported on intragenomic polymorphism in ITS sequences within the same strain of fungal and yeast species (Wang & Yao, 2005;Fell et al, 2007;Kageyama et al, 2007;Jacques et al, 2009;Connell et al, 2010;Saksinchai et al, 2012). Z. sapae sp.…”
Section: Genetic Diversity Sequence Analyses and Species Delineationmentioning
confidence: 99%